Detection of Edwardsiella tarda From African Catfish (Clarias garipienus) by Agar Gel Precipitation (AGP) Method in jambi - Surya Amanu; Miftahul Fikar; Rudi Barmara (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
For the past few years, Edwardsiella tarda has become major problem in African catfish culture in Jambi. Detection by biochemical characteristic can lead to inaccurate result and there is a necessity to develop more specific and accurate method, one of which is Agar Gel Precipitation (AGP) method. Six samples each were collected from two African catfish farm located in District Sungai Gelam and Telanai Pura in Jambi, which was showed clinical signs of E. tarda outbreak with more than fifty percent mortality rate. Heat stable soluble antigen was prepared from 2 groups of pure culture isolated from sample for AGP test. Antiserum for test wells was antiserum of E. tarda (ATCC 15947) that have been produced by inoculating whole-cell antigen (heat-stable) and flagellar antigen (formalin-killed) in rabbit. For control positive, soluble antigen prepared from E. tarda (ATCC 15947), and control negative from Aeromonas hydophila (ATCC 35654) and Edwardsiella ictaluri (NCIMB 13272). Both antiserums were able to show positive reaction visible by the formation of specific precipitin lines between antiserum and antigen wells, and there was no precipitin reaction for negative control. In conclusion AGP method is a one of reliable technique to identify E. tarda.